Fertility, economic development, and remittances in post-communist times - Azizbek Tokhirov; Jonas Suchanek (Journal of Maps)
This study investigates fertility responses to remittances across developed and developing countries in post-communist times. We first collected fertility, remittances, and income statistics over the 1995–2020 period and created a new vulnerability index that identifies less economically developed states with high fertility rates and dependent on remittances. We then examined the global fertility effects of remittances between 1995 and 2015 via Ordinary Least Squares, Fixed Effects, and Instrumental Variable estimation methods. The baseline regression results suggest that the relationship between remittances and fertility rates of remittances-receiving countries is generally inverse. We also found that the fertility-reducing power of remittances is heterogeneous worldwide. To illustrate the findings, we constructed two heat maps for 196 countries. The first one depicts the distribution of the vulnerability index, and the second one is dedicated to variations in the fertility effects of remittances across countries based on the vulnerability index.